1986
DOI: 10.3109/10826088609083537
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use and Abuse in College Students. II. Social/Environmental Correlates, Methodological Issues, and Implications for Intervention

Abstract: This review of alcohol use and abuse in college students presents a summary of the relationships between college student alcohol use and social/environment characteristics. A theoretical integration of the findings of this review with those of Part I of this series supports the prior paper's finding of two patterns of college drinking. This review further suggests that the two types may have differential predictive ability with regard to future problem drinking. Methodological issues in this type of research a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 42 publications
3
20
0
Order By: Relevance
“…The associations of NMPOU with rural residence and low SSS among female students represent potential socioeconomic determinants, similar to those identified for other forms of psychoactive drug use among young people [52][53][54]. Other studies have suggested that POs, compared with other drugs, may be more available or accessible in rural compared with urban areas, which may influence NMPOU [55,56].…”
Section: Discussionsupporting
confidence: 62%
“…The associations of NMPOU with rural residence and low SSS among female students represent potential socioeconomic determinants, similar to those identified for other forms of psychoactive drug use among young people [52][53][54]. Other studies have suggested that POs, compared with other drugs, may be more available or accessible in rural compared with urban areas, which may influence NMPOU [55,56].…”
Section: Discussionsupporting
confidence: 62%
“…Greek involvement has shown consistent associations with heavy alcohol use (Borsari & Carey, 1999;Brennan, Walfish, & AuBuchon, 1986;Cashin, Presley, & Meilman, 1998). Compared to other students, Greek members have more drinking problems (Faulkner, Alcorn, & Garvin, 1989;Lichtenfield & Kayson, 1994) and endorse more tolerant views on alcohol consumption (Klein, 1992).…”
Section: Greek Membershipmentioning
confidence: 99%
“…In contrast to the extensive literature on alcohol use by college students in the United States, [9][10][11][12][13][14][15] few studies have examined the drinking behaviour and attitudes of young adults in Australia. Where studies have been conducted, they tend to focus on students in tertiary education rather than similar aged youth in the workforce.…”
Section: Young Adultsmentioning
confidence: 99%